2019
DOI: 10.1158/1538-7445.am2019-5016
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5016: STACT-TREX1: A systemically-administered STING pathway agonist targets tumor-resident myeloid cells and induces adaptive anti-tumor immunity in multiple preclinical models

Abstract: Systemic delivery of STING agonists to tumor-resident myeloid cells will be required to elicit optimal type I interferon-mediated anti-tumor immunity in a metastatic disease setting. To this end, we have generated a microbial-based immunotherapy (STACT- Salmonella Typhimurium (Attenuated) Checkpoint Therapy) that utilizes a highly attenuated, clinically developed strain that is specifically enriched in tumors after intravenous administration. The strain has been modified to reduce pro-inflammatory TLR signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another novel bacterial-based immunotherapy is an attenuated Salmonella Typhimurium strain (STACT) that carries an inhibitor of TREX-1, the exonuclease that prevents activation of STING by degrading cytosolic DNA. Pre-clinical work found that intravenously delivery caused tumor colonization, tumor regression, and immunity to rechallenge 45,65 . Such microbial-based cancer therapies are advantageous as they can be administrated systemically and thus can target tumors throughout the body.…”
Section: Discussionmentioning
confidence: 99%
“…Another novel bacterial-based immunotherapy is an attenuated Salmonella Typhimurium strain (STACT) that carries an inhibitor of TREX-1, the exonuclease that prevents activation of STING by degrading cytosolic DNA. Pre-clinical work found that intravenously delivery caused tumor colonization, tumor regression, and immunity to rechallenge 45,65 . Such microbial-based cancer therapies are advantageous as they can be administrated systemically and thus can target tumors throughout the body.…”
Section: Discussionmentioning
confidence: 99%
“…The TREX-1 exonuclease prevents the activation of the STING pathway by degrading cytosolic DNA. Preclinical studies illustrated that intravenous injections of STACT-TREX-1 into CT26 and MC38 murine models produced very low systemic levels of inflammatory cytokines and demonstrated tumor-specific colonization, tumor regression, and durable immunity upon rechallenge (Makarova et al 2019 ).…”
Section: Therapeutic Regulation Of Cgas-sting Pathwaysmentioning
confidence: 99%
“…When further combined with an anti-PD-L1 antibody, an exceptional anti-tumor effect was observed ( 127 ). The utilization of bacteria to deliver STING agonists to tumor interiors is also under active investigation ( 136 , 137 ).…”
Section: Application Of Sting Agonists In Cancer Researchmentioning
confidence: 99%